Strategi Pondok Pesantren Dalam Membentuk Karakter Santri di Era Revolusi Industri 4.0 (Studi di Pondok Pesantren Manba'ul Hidayah Purwamekar Karawang) - Kasja Eki Waluyo (JURNAL ILMIAH EDUNOMIKA, 2021)
Currently, the absorption power of students is still good because most students are under 17 years. Moreover, their memory is still very good because the students still imitate the styles and behavior patterns of older people. This happens because they are still unstable depending on the person who brought them. The existence of pesantren in an era that has begun to advance and is starting to put aside traditional practices is a new challenge for a boarding school. With the entry of the era of the industrial revolution 4.0, digitization of various elements is feared by students for imitatating negative influences. Therefore, researchers are interested in further researching to find out the strategy of Islamic boarding schools in shaping the character of students in the era of the industrial revolution 4.0., how is the strategy of the pesantren in shaping the character of students in the era of industrial revolution 4.0. This research is a field research, with a qualitative descriptive type of research which employs case study method. Keywords: Strategy, Character of Santri, Industrial Revolution Era